Fractographic approach to metallurgical coke failure analysis. Part 3: Characterisation of fracture mechanisms in a blast furnace coke. (15th September 2016) - Roest, Richard; Lomas, Hannah; Gupta, Sushil; Kanniala, Riku; Mahoney, Merrick R.
Highlights: A fractographic approach identified blast furnace coke failure mechanisms. Breakage behaviour of cokes was influenced by porosity and interface properties. Breakage behaviour of blast furnace cokes was notably different to feed coke. Abstract: Metallurgical coke samples across the tuyere level of an operating blast furnace were analysed using a fractographic approach to identify and quantify various coke failure mechanisms. Tuyere level cokes displayed different failure mechanisms compared to the feed coke, implying a strong influence of the blast furnace reaction environment on the modification of coke failure mechanisms. The conchoidal and brittle overload type failures were noted to have an effect on the propagation of transgranular and intergranular crack growth in the coke microstructure. Feed coke breakage behaviour was strongly influenced by existing fissures and conchoidal fracture, while the breakage of the deadman coke lumps was dominated by pore wall collapse through intergranular crack growth in combination with erosive wear. The porosity at the IMDC–RMDC interface in coke has been identified as a critical parameter contributing to coke failure at tuyere regions. This fractographic study demonstrates that the fracture faces show evidence of the varying failure mechanisms presented in the preceding manuscripts (Part 1 and Part 2), in addition to the erosive wear resulting from the blast furnace exposure. However, further studies are required to establish the association between the identified coke failure mechanisms and coke texture, which has implications for improving coke performance in a blast furnace.